Răspuns :
A - B = 15
A / B = 2 rest 7 => A= 2*B+7
înlocuim in diferența
2*B+7 - B = 15
2*B - B + 7 = 15
B +7= 15
B = 15-7
B = 8
A- B = 15 si înlocuim B cu 8
A - 8 = 15
A = 15+8
A= 23
A / B = 2 rest 7 => A= 2*B+7
înlocuim in diferența
2*B+7 - B = 15
2*B - B + 7 = 15
B +7= 15
B = 15-7
B = 8
A- B = 15 si înlocuim B cu 8
A - 8 = 15
A = 15+8
A= 23
Fie a si b cele doua numere
a-b=15
=>a=b+15
a:b=2 rest 7
=> a=2b+7
Le scadem pe cele doua ecuatii si obtine 0=8-b
b=8
a=23
a-b=15
=>a=b+15
a:b=2 rest 7
=> a=2b+7
Le scadem pe cele doua ecuatii si obtine 0=8-b
b=8
a=23